Factors influencing students’ decisions to start online businesses in the digital ERA at Thanh Dong University - Thu, Pham Thi (Edelweiss Applied Science and Technology, 2025)
This study examines the factors influencing Thanh Dong University students’ decisions to start online businesses in the digital era. A mixed-method design was adopted, in which the main phase used a cross-sectional survey with convenience sampling, yielding 300 valid questionnaires from second- to fourth-year students. This study employs the Structural Equation Modeling (SEM) technique using the SMARTPLS3 software to analyze the influence of factors: Educational Support, Relationship Support, Structural Support, and Entrepreneurial Experience on the factor of Entrepreneurial Intention. The factor of Entrepreneurial Intention affects the Decision to start an online business. The empirical results indicate that educational and relational support and prior entrepreneurial experience positively and significantly enhance entrepreneurial intention, while structural support shows no significant effect. Entrepreneurial intention, in turn, strongly promotes students’ decisions to start online businesses. These findings suggest that universities should strengthen practice-oriented entrepreneurship education, mentoring networks, and experiential start-up activities to foster students’ entrepreneurial intention and translate it into actual online business ventures in the digital age. The study contributes to enriching the literature on student digital entrepreneurship in emerging economies.